Pendampingan Penyusunan Modul Ajar Kurikulum Merdeka untuk Meningkatkan Kompetensi Pedagogik Guru di Jenjang Pendidikan Dasar - Hasanah, Uswatun; Sibilana, Annas Ribab; Karimah, Azzahrotul; Ariyanti, Lita; Nurhidayati, Nurhidayati (LPPM UNIVERSITAS DIAN NUSWANTORO, 2024)
Meaningful learning has always been the main focus in the implementation of education and learning. Meaningful learning requires an education that not only ensures students know or memorize information but also enables them to understand, analyze, evaluate, create, and apply it in everyday life. The success of education is highly determined by the teacher's pedagogical competence, starting from the preparation of teaching materials, specifically the teaching modules. The problem observed in the field is that not many teachers are able to compile teaching modules properly. This is due to several factors, including inadequate skills, a lack of training programs that can enhance teachers' competencies, and insufficient dissemination of information regarding the format of teaching modules in the Merdeka Curriculum. The purpose of this service is to explain the technical assistance and the outcomes of mentoring in the preparation of teaching modules for the Merdeka Curriculum to improve the pedagogical competence of teachers in Madrasah Ibtidaiyah. The result of this service is an increase in teachers' knowledge in developing teaching modules that are suitable for the conditions of the students and the school.